Understanding the Learners’ Intelligence, Stress and Attitude to Learning on Worldwide Knowledge, Research, and Experience - Saravanan, T; Nagadeepa, N (International Journal of Computer Sciences and Engineering, 2025)
Research on various aspects of the multimedia learning materials such as animation, sound, graphics, interactive video and its impacts on learning has been conducted. For the development of any comprehensible educational system, the learning materials and methodology play a very important role. The students’ inner psychology is an integral part of any learning system aiming at personalized information material delivery. Personalized information material delivery can be described as a process of building the learning materials according to the students’ personal inner psychology, his/her behavioural aspects, goals, likes and dislikes. The inner psychology of a student is generally represented in the form of his/her intelligent quotient, emotional quotient, personality, stress and attitude quotient. The research works differ in the way they represent the student psychology, how they update the student’s inner feeling and the teaching–learning strategies they adapt for providing the personalized information learning materials.